To determine the level of job satisfaction: the case of Grand Darul Makmur Hotel Kuantan’s staffs / Nur Erina Husna Mohamed Razif - Mohamed Razif, Nur Erina Husna (2020)
This research is about a study on the employees’ job satisfaction on the Grand Darul Makmur Hotel Kuantan’s staffs was conducted internally by using GDM Hotel staffs as respondent This research was to determine that demographic as the main factor that affected their job satisfaction. This is a correlation research, which is to determine the relationship between variables includes of variety methods that described the relationship between variables. The sampling frame is the GDM Hotel’s staffs with population of 150 staff using the convenience sampling technique. The sample size is 100 and the unit analysis is individual with the instrument of likert scale question and closed ended question. Questionnaire is using to collect the data and correlation analysis is used to analyse the data.